A new non-phagocytic TLR6 with broad recognition ligands from Pacific oyster Crassostrea gigas. (December 2016) - Wang, Weilin; Zhang, Tao; Wang, Lingling; Xu, Jiachao; Li, Meijia; Zhang, Anguo; Qiu, Limei; Song, Linsheng
Abstract: Toll like receptors (TLRs) are evolutionarily prevalent recognition molecules in the Animalia and Plantae kingdom, which play vital roles in immune defense and homeostasis maintenance. Recently, the expansion of TLRs has been reported in invertebrate genomes, but the characters and immune functions of these expanded TLRs were still not well known. In the present study, a new member of TLR family with five LRR domains was identified in Crassostrea gigas (designated Cg TLR6). It shared homology with TLRs from other organisms with the closest phylogenic relationship with molluscan TLRs. The recombinant protein of Cg TLR6 (r Cg TLR6) displayed direct bind activity to gram-negative bacteria Vibrio anguillarum and Vibrio splendidus, gram-positive bacteria Staphylococci aureus and Micrococcus luteus, and fungi Pichia pastoris, but not to fungi Yarrowia lipolytica . It also exhibited affinity to lipopolysaccharide (LPS) and peptidoglycan (PGN), while no affinity to mannan (MAN). The mRNA of Cg TLR6 was mainly detected in hemocytes and hepatopancreas, and was significantly induced ( p  < 0.01) in hemocytes after the oyster was stimulated with LPS, PGN or bacteria V . splendidus . Immunofluorescence analysis indicated that Cg TLR6 was mainly located at the membrane of hemocytes. The blockage of Cg TLR6 by anti-r Cg TLR6 antibody did not significantly inhibit the phagocytic rates of hemocytes toward recognized gram-negative bacteria V . anguillarum and V . splendidus, and unrecognized fungi Y . lipolytica . These results collectively implied that Cg TLR6 was a novel non-phagocytic receptor of C . gigas to mediate humoral immune response by recognizing pathogen-associated molecular patterns on the invaders. Highlights: A new molluscan TLR with five LRR domains was identified in Pacific oyster Crassostrea gigas. Cg TLR6 was located at the membrane of hemocytes. It displayed significant affinity to broad PAMPs and microbes. Its mRNA transcripts in hemocytes significantly increased after PAMPs or bacteria stimulation. In vitro Cg TLR6 blocking exhibited little impact on phagocytic capabilities of hemocytes.